The Influence of Learning Discipline and Teacher Teaching Style on The Learning Achievement of Class VIII Students of SMP Negeri 12 Pematang Siantar in The 2023/2024 Academic Year. - Inka Pebrianti Sidabutar (International Journal of Integrated Science and Technology, 2023)
This research aims to gain knowledge regarding the influence of learning discipline and teacher teaching styles on the learning achievement of class VIII students at SMP Negeri 12 Pematang Siantar for the 2023/2024 academic year. This type of research is quantitative research with a quantitative descriptive data analysis approach with the testing media used is SPSS 21. The population in this study was 277 people, and the sample used was 163 people. The sample collection technique used was Proportionate Stratified Random sampling. The data collection technique used was a questionnaire. The hypothesis data collection technique uses multiple regression analysis and the coefficient of determination (R2).The results of this research state that: 1) there is a positive influence of learning achievement on learning discipline. This result can be seen in the t test where the t value of parental income (15.011) > t table value (1.65437). 2) there is a negative and insignificant influence of the teacher's teaching style on learning achievement. This result can be seen in the t test where the t value of social style (-0.725) > t table value (1.65437) which means that this variable is not significant. 3) learning discipline and the teacher's teaching style together influence learning discipline. This result can be seen in the F test where the Fcount value (187.479) > Ftable value (3.05). The R Square coefficient of determination test was found to be 0.701, which means that 70.1% of the variables are the influence of learning discipline and teacher teaching styles on the learning achievement of class VIII students at SMP Negeri 12 Pematang Siantar and 29.9% is the influence of other variables not examined in this research. Keywords: Learning Achievement, Learning Discipline, Teacher Teaching Style